BIO EFFICACY OF ENTOMOPATHOGENIC FUNGUS BEAUVERIA BASSIANA AND CERTAIN INDIGENOUS PRODUCTS AGAINST PLUTELLA XYLOSTELLA (LINN) INFESTING CABBAGE - KAMIN ALEXANDER,; S. C. MASIH,; ABHISHEK CHRIS, (The Bioscan, 2012)
Studies were conducted to know the comparative bio-efficacy of Entompathogenic fungus Beauveria bassiana and certain indigenous products against the larvae of diamond back moth, Plutella xylostella (Linn) on Cabbage (Brassica Oleracea). A lab trial was conducted during the 2008-2010 at Allahabad Agriculture Institute Deemed University. All the treatments were found significantly superior over control. Among the treatments the highest larval mortality of 100% with the treatment Ts (DDVP O.05%) and the minimum larval mortality of 21.429% was recorded with the treatment (NL+CBM 4%). The extent of mortality of Plutella xylostella (Linn) appeared to be affected by the number of conidia striking on the insect body. Each episode of treatment was replicated three times and percent net mortality of different larval instar (1st, 3rd, 5th) was recorded after the interval of 24, 48 and 72h, percent net mortality at 72h was recorded highest over 48 and 24h and at the same time mortality in 1st instar was found more in comparison to 3rd and 5th instar larvae.